2009
DOI: 10.1080/10715760902942808
|View full text |Cite
|
Sign up to set email alerts
|

Increasing expression of H- or L-ferritin protects cortical astrocytes from hemin toxicity

Abstract: Iron toxicity may contribute to oxidative injury in cells surrounding an intracerebral hematoma. Cells detoxify iron by sequestering it in ferritin, a 24-mer heteropolymer constructed of H and L subunits. The relative antioxidant efficacy of H and L-ferritin has not been defined, and was tested in this study using an established model of hemin toxicity. Consistent with prior observations, cultures treated with 30 μM hemin sustained loss of approximately half of cells by six hours, as measured by LDH and MTT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Nevertheless, studies of various cell lines and in vivo studies have shown that a number of conditions or agents known to increase cell H 2 O 2 and O 2 Á -levels induce the reversible inactivation of IRP1 (12,18,63,193,200), and this makes it possible to conclude that IRP1 downregulation (aimed at decreasing TfR1 while increasing ferritin levels, and hence diminishing the LIP) is a common response designed to prevent the enhanced formation of ROS. In line with this, increased ferritin synthesis has been documented in a number of cell types exposed to oxidative stimuli (14,205), whereas the overexpression of either the ferritin H (36, 52, 150) or ferritin L subunit (110,150) reduces oxidative damage.…”
Section: B Oxidative Stressmentioning
confidence: 89%
“…Nevertheless, studies of various cell lines and in vivo studies have shown that a number of conditions or agents known to increase cell H 2 O 2 and O 2 Á -levels induce the reversible inactivation of IRP1 (12,18,63,193,200), and this makes it possible to conclude that IRP1 downregulation (aimed at decreasing TfR1 while increasing ferritin levels, and hence diminishing the LIP) is a common response designed to prevent the enhanced formation of ROS. In line with this, increased ferritin synthesis has been documented in a number of cell types exposed to oxidative stimuli (14,205), whereas the overexpression of either the ferritin H (36, 52, 150) or ferritin L subunit (110,150) reduces oxidative damage.…”
Section: B Oxidative Stressmentioning
confidence: 89%
“…Evidence suggests that FHC, which contains a ferroxidase center, oxidizes Fe II for FLC which, in turn, mineralizes and stores Fe III [152, 153]. In the brain, ferritin is found in the choroid plexus [154], astrocytes [155], oligodendrocytes, pyramidal neurons, microglia, and BMVEC [1]. Ferritin is trafficked across BMVEC via transcytosis from P1-P7; this method of trafficking is significantly diminished after complete ensheathment of the BMVEC by astrocytic endfeet at P14 [10].…”
Section: Proteins Involved In the Efflux Of Iron From Bmvecmentioning
confidence: 99%
“…Since each ferritin molecule can sequester over 4000 ferric ions in it mineral core [13], we hypothesized that the increase in the labile iron pool that we have previously observed in these cultures after hemin treatment [16] would be reduced by metHb or thrombin preconditioning. Cytosolic labile iron, as detected by calcein fluorescence quenching [21], was significantly decreased in cultures pre-treated with 3 μM metHb followed by 30 μM hemin, compared with control cultures pretreated with MEM10 medium alone before hemin exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cortical glial cultures (> 90 % GFAP +) were prepared from 2–3 day old C57BL/6 X 129/Sv mice that were bred in our animal facility, following a protocol that was approved by the local Institutional Animal Care and Use Committee and previously described in detail [16]. Approximately two-thirds of the culture medium was replaced at 5–6 days in vitro and then twice weekly, using growth medium containing minimal essential medium (MEM), 23 mM glucose, 2 mM glutamine, and 10 % equine serum (Hyclone, Logan, UT, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation